Entre a posição e as práticas: classes médias nas perspectivas de Erik Olin Wright e Pierre Bourdieu - Luís Fernando Santos Corrêa da Silva (Ciências Sociais Unisinos, 2020)
The article presents the theorithical contributions of Erik Olin Wright and Pierre Bourdieu to the contemporary development of a sociology ofsocial classes, especially to the analy-sis of social classes. Erik Olin Wright 's neomarxist theory seeks to overcome the social classes growth in the capitalist development process through the idea of "contradictory class location", as, regardless of the fact that the middle class sells its labour force, it also owns quality and authority assets which differentiate it from the traditional working class. However, Pierre Bourdieu's theory ofsocial space emphasising the symbolic dimension of class relations highlights some features that would be particular to middle classes, such as the moral rigidity the asceticism, valorisation of education and culture and the focus on individual merit as a form of upward social mobility. These characteristics could be construed by middle class as differentiating criteria and as a specific type ofcapital, which has contributed to separate middle class from the popular class. It is concluded that while Wright takes interest in reshaping the theoretical grounds ofMarxism to understand the class structure in the contemporary capitalism, by problematising the middle class as a heterogeneous social layer, Bourdieu is interested in the symbolic constructions sustaining a concept ofmiddle class which undertakes strategies to diferentiate itself from popular classes by valorising scarce or found to be superfluous cultural goods by those who are close to the border of basic-needs.